# Solution for 55x^2+79x+28

```//--------------
// Final Result   (11x + 7) • (5x + 4)
//--------------

//--------
// Drill :  55x^2+79x+28
//--------
Simplify :

((55 • (x2)) +  79x) +  28

//------------
// Step #  01:    Simplify   55x2+79x  +  28
//------------

# 01.01   Factoring    55x2+79x+28

Method : Factoring by splitting the middle term

The first term is    55x2  ,its coefficient is 55
The middle term is   +79x  ,its coefficient is 79
The last term, also called 'the constant', is  +28

Step-1   : Multiply the coefficient of the
first term by the constant

55 • 28 = 1540

Step-2   : Find two factors of  1540  whose
sum equals the coefficient of the
middle term, which is 79

-1540   +   -1   =-1541
-770   +   -2   = -772
-385   +   -4   = -389
-308   +   -5   = -313
-220   +   -7   = -227
-154   +  -10   = -164
-140   +  -11   = -151
-110   +  -14   = -124
-77   +  -20   =  -97
-70   +  -22   =  -92
-55   +  -28   =  -83
-44   +  -35   =  -79
-35   +  -44   =  -79
-28   +  -55   =  -83
-22   +  -70   =  -92
-20   +  -77   =  -97
-14   + -110   = -124
-11   + -140   = -151
-10   + -154   = -164
-7   + -220   = -227
-5   + -308   = -313
-4   + -385   = -389
-2   + -770   = -772
-1   +-1540   =-1541
1   + 1540   = 1541
2   +  770   =  772
4   +  385   =  389
5   +  308   =  313
7   +  220   =  227
10   +  154   =  164
11   +  140   =  151
14   +  110   =  124
20   +   77   =   97
22   +   70   =   92
28   +   55   =   83
35   +   44   =   79   Tiger found it !!

Step-3   :  Rewrite the polynomial splitting
the middle term using the two
factors found in Step-2, (35) and (44)

55x2 + 35x  +  44x + 28

Step-4   : Add up first 2 terms, pulling
out like factors  :    5x•(11x+7)

Add up last 2 terms, pulling
out common factors:   4•(11x+7)
———————————
Factorization is  :             (5x+4)•(11x+7)

//--------------
// Final Result   (11x + 7) • (5x + 4)
//--------------

Processing ends successfully```